41 Renal insufficiency, bleeding and prescription of discharge medication in patients undergoing percutaneous coronary intervention in the national heart, lung, and blood institute (NHLBI) dynamic registry. (28th September 2016) - Bajrangee, A; Margey, R; Selzer, F; Jneid, H; Marroquin, O; Mulukutla, S; Warren, W; Jacobs, A; Maree, A
Abstract : Aims: To establish the relationship between renal insufficiency, bleeding and prescription of cardiovascular medication. Methods and results: This was a prospective, multi-centre, cohort study of consecutive patients undergoing PCI during three NHLBI Dynamic Registry recruitment waves. Major and minor bleeding, access site bleeding and rates of prescription of cardiovascular medication at discharge were determined based on estimated glomerular filtration rate (eGFR). Renal insufficiency was an independent predictor of major adverse cardiovascular events (MACE). Bleeding events and access site bleeding requiring transfusion were significantly associated with degrees of renal insufficiency (p < 0.001). There was an incremental decline in prescription of cardiovascular medication at discharge proportionate to the degree of renal impairment (aspirin, thienopyridine, statin, coumadin (overall p < 0.001), beta blocker (overall p = 0.003), ACE inhibitor (overall p = 0.02). Bleeders were less likely to be discharged on a thienopyridine (95.4% versus 89.9% for bleeding, p < 0.001 and 95.3% versus 87.9% for access site bleeding, p = 0.005), but not aspirin (96.3% versus 96.2%, p = 0.97 and 96.3% versus 93.6%, p = 0.29 respectively). Failure to prescribe anti-platelet therapy at discharge was strongly associated with increased MACE at one year. Conclusions: Renal insufficiency predicts bleeding in patients undergoing PCI. Patients with renal insufficiency are less likely to receive recommended discharge pharmacotherapy.